Place in the history of the person and his artistic reconstruction (Eurasian Journal of Philology Science and Education, 2018)
The man in the Kazakh writer Muhtar Magauin’s romances «Spring Snow» and «Time of Troubles»acts as the subject of history, as the main way of life and self-development of their relation to themselves, to the people, the people, to mankind evidence of the relation of the individual to the story, which she embodies and works for others. Place the individual in history, its principles, activities, appearance and artistic re-creation associated with the originality of the author’s conception. The writer in the image of man as a subject of historical fact, found the artistic truth, which is not contrary to the historical truth, and carries the truth of images of known history, but created according to the laws of art. Before M. Magauin was a difficult task – to specific human characters to show how events actually refracted in the fate of the characters, as in a turbulent maelstrom of history man her husband as he battled that worried. It is this quality – the ability to penetrate into the inner world of man, the writer is different from the scientist and historian.